Концепт ТОЛЕРАНТНІСТЬ: генетичний аспект дослідження - Юдко, Л.В. (Мовознавство, 2017)
У статті проаналізовано підходи до дослідження концепту ТОЛЕРАНТНІСТЬ в англійській, німецькій, російській, українській лінгвокультурах, визначено етимологію лексеми - вербалізатора концепту, ціннісний складник, спільне та відмінне для кожної лінгвокультури. The timeliness of the proposed research is determined hy the study of value-conscious characteristics of the concept TOLERANCE as a part of the socio-cultural gestalt which defines a constructive vector in the multi-ethnic communication space. The purpose of the article is to determine the value-conscious component of the concept TOLERANCE for English, German, Russian and Ukrainian linguistic cultures. The tasks of the article are: 1) to analyze and systematize modem scientific approaches to the study of the concept TOLERANCE; 2) to define the role of the concept TOLERANCE in national discourse practices by analyzing lexicographical sources and scientific discourses. The subject of the article is the concept TOLERANCE in the modem scientific paradigm and communicative space of Great Britain, Germany, Ukraine and Russia; the target of research is the ways of foregrounding of the concept TOLERANCE in Russian and Ukrainian linguistic cultures. In the article, approaches to the study of the concept TOLERANCE have been systematized; the etymology of the lexeme-verbalizer of the concept in English, German, Russian and Ukrainian linguistic cultures has been analyzed; common and distinctive components of meanings are established; the value-conscious component of the concept TOLERANCE for each linguistic culture has been defined.